Aerosol blocking assessment by different types of fabrics for homemade respiratory masks: spectroscopy and imaging study - Giuliani, Carla Denari; Foschini, Mauricio; Monte, Adamo Ferreira Gomes; Mendes, Ana Caroline Moreira; Maletta, Alexandre; Janones, Renata Scarabucci; Duarte, Bruna Aparecida Rodrigues; Del-Claro, Kleber (Open Science Journal, 2021)
Objectives: Due to the crisis in protective equipment caused by a pandemic, it generates needs for equipment rationing among professionals working in the health area, with the need for many health professionals to use homemade masks. Therefore, this is a comparative study regarding the relative efficiencies of commercial respiratory masks (medical masks) and homemade fabric masks. Methods: A liquid aerosol line was created that passes through a chamber with 6 optical windows that allows the fixation of tissue or masks in the aerosol flow. The measures used two spectroscopic techniques that made it possible to relate the amount of aerosols with the scattering of light.. Results: Fabrics with a higher percentage of cotton, and a greater number of layers and more closed wefts proved to be more efficient in blocking aerosols, however, fabrics without treatments obtained results far below the real needs of professionals working in the health area, with efficiency below 75% for liquid aerosols among the tissues tested. Conclusion: Homemade masks prove to be effective in reducing the spread of the virus among ordinary citizens in past infections, the efficiency of homemade masks is very low for health professionals who are directly exposed to the biological agent, so, it is necessary for public administrations to seek new alternatives with greater efficiency for this type of professional during the absence of surgical masks and n95.